(untitled) (Journal of the Management Sciences, 2025)
Health is a fundamental human right influenced by social, economic, and environmental factors. This paper was illuminated by the Social Determinants of Health (SDOH) Theory which explains how disparities in income, education, employment, and living conditions shape health outcomes. Inequalities in healthcare access, gender discrimination, and poverty disproportionately impact marginalized communities, perpetuating cycles of poor health. Social capital, comprising interpersonal relationships and community networks, plays a crucial role in mitigating these disparities by fostering support, trust, and shared resources. Conversely, strong social connections enhance mental health, improve well-being, and reduce health inequalities. However, structural barriers such as political exclusion, economic instability, and environmental hazards reinforce social disparities, limiting individuals’ access to essential resources. Historically, inequalities have persisted despite economic progress, reflecting systemic mechanisms that favour privileged groups. This paper therefore established that public policy interventions, including social welfare programs, education, and healthcare reforms, are vital for addressing these disparities. This is so as economic instability, inflation, and unemployment further exacerbate inequalities, negatively affecting health and social mobility.